The late diagnosis of double cortex syndrome in a 36-year-old woman with resistant atonic seizures - N. A. Shnayder; D. V. Dmitrenko; Yu. B. Govorina; E. A. Kantimirova; O. V. Alekseeva; A. A. Molgachev; A. A. Makarkin (Неврология, нейропсихиатрия, психосоматика, 2015)
Subcortical laminar heterotopia (double cortex syndrome) is an orphan disease with an incidence of 1 to 200,000 people in the population. The cause of the disease is mutation of the gene DCX (synonyms: DBCN, XLIS) in chromosome Xq22.3-q23. The type of inheritance is X-linked dominant. Correct diagnosis requires a high degree of skills of a neurologist/epileptologist and a radiologist. The paper describes a clinical case of the late diagnosis of double cortex syndrome in a 36-year-old woman with a long history of resistant atonic seizures and mental retardation.